2018
DOI: 10.1111/papt.12205
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem fully mediates positive life events and depressive symptoms in a sample of 173 patients with affective disorders

Abstract: Objectives Previous research showed that positive and negative life events influence the development of depression. However, it is less clear how life events interact with depressive symptoms and self‐esteem. Design and methods The present study aimed to investigate the mediating effects of self‐esteem on the relationship between life events and depressive symptoms in adulthood. The Traumatic Antecedent Questionnaire, Multidimensional Self‐esteem Scale (MSWS), and Becks Depression Inventory were administered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…This relationship is mediated by perceived stress (Kim et al, 2016;Thimm et al, 2018) which increases when activities and social support decrease (Chao, 2014;Mayer et al, 2018). In addition to social dysfunction, the majority of people suffering from depression also experience sleep problems (Meerlo et al, 2015;Zhai et al, 2015), weight dysregulation (Ibrahim et al, 2016), and low self-esteem (Sarubin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This relationship is mediated by perceived stress (Kim et al, 2016;Thimm et al, 2018) which increases when activities and social support decrease (Chao, 2014;Mayer et al, 2018). In addition to social dysfunction, the majority of people suffering from depression also experience sleep problems (Meerlo et al, 2015;Zhai et al, 2015), weight dysregulation (Ibrahim et al, 2016), and low self-esteem (Sarubin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed that self-esteem is negatively associated with antisocial behavior (Barry et al, 2003;Jia et al, 2020), indicating that high self-esteem is less likely to lead to antisocial behavior tendencies. Besides, previous studies have confirmed the mediating role of self-esteem between negative life events and negative emotions (Han et al, 2018;Sarubin et al, 2020), as well as a mediating role between perceived parenting and antisocial behavior tendencies (Hunter et al, 2015). Both the correlation of negative life events with self-esteem and the correlation of self-esteem with antisocial behavior tendencies have been studied.…”
Section: Introductionmentioning
confidence: 75%
“…On the contrary, it will be of important practical value to lessen the harmful effect of negative life events on antisocial behavior tendencies in adolescents. Despite the well-recognized connection between antisocial behavior and negative life events ( Norman et al, 2012 ; Gilbert et al, 2015 ; Sarubin et al, 2020 ), many individuals who deal with highly stressful situations do not develop antisocial behavior, so the particular characteristics of this association is still uncertain. As a result, there is an urgent need to clarify the influence factor and internal mechanism of negative life events leading to antisocial behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the available literature includes several examples of successful pairing procedures, including with clinical populations, related to improving negative self-concepts [15], body ideals [16], and food preferences [17]. Given the relevance of these and similar evaluations for the emergence and maintenance of disordered cognitions and behaviors [23][24][25][26][27][28][29][30][31][32][33], pairing procedures may indeed offer a simple yet effective means of complementing CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this idea, an increasing number of studies show that altered evaluations link to disordered cognitions and behaviors. For example, a generalized negative self-evaluation, i.e., negative self-esteem, both characterizes and predicts the onset of depressive symptoms [23][24][25]; shifted evaluations of body ideals and foods are associated with the development and maintenance of eating disorders [26][27][28][29][30][31]; phobic patients show evaluative biases in processing fear-relevant stimuli and situations [32,33]. These and similar evaluations need not be consistent with an individual's explicit beliefs or goals (e.g., people frequently desire sweets despite knowing the benefits of restraint [34]) and are less susceptible to conscious introspection and control [19].…”
Section: The Clinical Potential Of Pairing Proceduresmentioning
confidence: 99%